How Eritreans plan, fund and manage irregular migration, and the extent of involvement of ‘organised crime’ - Whittle, Joseph (Crime prevention and community safety, 2020)
The increased government, media and public focus on migration from Africa to the EU in the past few years has led to an explosion in reporting from governments, NGOs, academics and quasi-academia. Within this context, there are a number of basic assumptions and discourses in relation to these migratory processes from Africa. The first assumption, often put forward by the media, is that migrants from Africa intend to cross the Mediterranean Sea in an effort to reach Western European countries. The second assumption is that in their effort to cross the Mediterranean, African migrants are facilitated by ‘criminal networks’. The third (and extremely popular in the last few years) assumption is that information and communication technologies have been instrumental in the planning of irregular migration and identifying smugglers to facilitate migration. The final assumption, which has also garnered increasing attention in recent years, is that understanding human smuggling finances can inform policies specifically targeting migrant smuggling. This article, which is based on in-depth interviews with Eritreans, who have migrated illegally in Egypt, aims to add to the understanding about how Eritrean people plan, fund and manage irregular migration journeys. In the process, it will attempt to debunk some of the common assumptions around irregular migration.